Three-layer torsional angle MoS2 and preparation method thereof

The three-layer torsion MoS2 was grown on the SiO2/Si substrate by a one-step CVD method, and the adjustment of the sulfur source curing ratio was used to solve the problems of the preparation difficulty of three-layer torsion MoS2 and the control of interlayer torsion structure in the prior art, and the preparation of high-quality and controllable three-layer torsion MoS2 material was achieved.

CN119843243APending Publication Date: 2025-04-18NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510110760.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art is difficult to achieve efficient preparation of three-layer torsion MoS2, especially in precise control of interlayer torsion structures.

Method used

One-step chemical vapor deposition (CVD) method is used to directly grow three layers of torsion MoS2 on SiO2/Si substrate, and the interlayer torsion structure is finely adjusted by adjusting the curing ratio and reaction conditions of the sulfur source.

Benefits of technology

It realizes high-quality preparation of three-layer torsion MoS2, with uniform material surface, no pollution, and controllable interlayer torsion structure, suitable for the development of high-performance electronic and optoelectronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843243A_ABST
    Figure CN119843243A_ABST
Patent Text Reader

Abstract

The invention discloses three-layer torsional angle MoS2 and a preparation method thereof, the method adopts a chemical vapor deposition method, and utilizes a sulfur source curing proportion regulation strategy to control the three-layer torsional angle MoS2 to obtain three-layer torsional angle MoS2 materials with different interlayer torsional structures. The method is simple in process and low in cost, secondary nucleation and non-uniform growth are avoided, and high quality and uniformity of the prepared material are ensured. By means of the method, the three-layer torsion angle MoS2 with multiple interlayer torsion structures can be controllably prepared, an effective way is provided for adjusting interlayer interaction strongly coupled with Moire superlattices, and therefore the unique associated electronic property and the multi-body effect related to excitons of the Moire superlattices are expected to be adjusted and controlled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nano materials and relates to a three-layer twisted-angle MoS2 and a preparation method thereof. Background Art

[0002] In 2020, Nat. Phys., 2020, 17, 374 reported the potential of three-layer twisted graphene in regulating electronic properties. Similar to twisted bilayer graphene, three-layer twisted graphene also exhibits highly tunable electronic properties and becomes a promising platform for realizing correlated and topological states. In three-layer graphene, similar mechanisms can cause the formation of flat bands and stimulate correlation phenomena, but the system becomes more complex due to the addition of the third layer of freedom. This additional degree of freedom may lead to richer physical phenomena than bilayer graphene. This research idea provides important inspiration for the study of three-layer twisted MoS2. As a transition metal chalcogenide, MoS2 also shows great potential in interlayer coupling, electronic correlation and optical properties under the regulation of twist angle. However, compared with twisted bilayer MoS2, the study of three-layer twisted MoS2 is more complicated. The stacking methods of the three-layer structure are more diverse, and the physical phenomena caused by different interlayer twist angle combinations are richer. Although artificial stacking has been widely used to construct twisted multilayer systems, the transfer process is complicated and it is difficult to achieve systematic research and optimization. In contrast, the chemical vapor deposition (CVD) method provides a new solution for the preparation of three-layer twisted MoS2. Through CVD technology, the required twisted structure can be grown directly on the substrate in one step, reducing the contamination and interface defects caused by subsequent processing steps, thereby facilitating the preparation of large-area, continuous and highly uniform thin films, which is essential for the development of high-performance electronic and optoelectronic devices. Although researchers have been able to make some progress in the preparation of three-layer twisted TMDCs materials using CVD technology by adjusting experimental conditions, independent twist angles are not formed between the layers. The paper "J.Phys.Chem.C, 2023,127,23420" successfully prepared three-layer twisted MoS2 by changing the carrier gas flow rate of the system, but it adopted a dual-temperature zone process, which increased the complexity of the experiment. The paper "Adv. Opt. Mater., 2024, 12, 2400907" successfully prepared a three-layer twist angle MoS2 with a 3R configuration between the middle layer and the bottom layer and an interlayer twist angle of 10° to 40° from the top layer to the middle layer with the assistance of NaCl, but not all interlayer structures show a relative twist relationship. Because the CVD process is restricted by various factors, the precise synthesis of three-layer twist angle TMDCs with different twist stacking structures faces great difficulties. Therefore, it is still very challenging to achieve efficient preparation of three-layer twist angle TMDCs with different twist stacking structures. To this end, the inventors have devoted themselves to research and invented a one-step CVD method to prepare three-layer twist angle MoS2 with different twist stacking structures, and obtained three-layer twist angle MoS2 with different twist stacking structures. Summary of the invention

[0003] The present invention provides a method for preparing a three-layer twisted MoS2 interlayer twisted structure that can accurately control the twist angle. The experimental process is simple, the raw materials are easy to obtain, and the prepared twisted MoS2 has a clean surface, high quality, and a controllable twisted stacking structure.

[0004] To achieve the above purpose, the following steps are specifically included:

[0005] A method for preparing three-layer twisted-angle MoS2, the preparation method comprising:

[0006] Step 1: The preparation space is a closed quartz tube, carrier gas is introduced into both ends of the quartz tube, a quartz crucible is placed at the inflow end of the carrier gas, and sulfur powder is placed in the quartz crucible;

[0007] Step 2: The Si surfaces of two SiO2 / Si substrates are laminated and stacked in a quartz test tube with openings at both ends, and a molybdenum source is placed in the tube, where the molybdenum source is located at the inflow end of the carrier gas;

[0008] Step 3: The quartz test tube and the quartz crucible are both placed in the furnace of the heating furnace, the sulfur powder is heated to 200°C until it is completely melted, then naturally cooled and solidified, and the solidified sulfur powder is mixed with the sulfur powder; the amount of sulfur powder solidified after heating is 0.6-2.4g, the amount of sulfur powder is 0.6-2.4g, the total amount of sulfur powder is 1.0-3.0g, and the distance that the sulfur powder extends into the furnace is 2.0-2.1cm;

[0009] Step 4: Set the temperature control program, control the heating rate at 25℃ / min, and after the temperature reaches 800℃ at a uniform rate, carry out material growth, and then cool naturally to obtain three-layer twisted MoS2 on the SiO2 / Si substrate.

[0010] Optionally, for the twisted-angle MoS2 with twisted structures between all three layers, the ratio of sulfur powder to sulfur powder solidified after heating is 2:3;

[0011] For twist-angle MoS2, where only two of the three layers have a twisted structure, the ratio of sulfur powder to sulfur powder solidified after heating is 4:1, 3:2, or 1:4.

[0012] Optionally, the sulfur source extends into the furnace by 2.0 to 2.1 cm; the molybdenum source and the sulfur source are 12 cm apart.

[0013] Optionally, the molybdenum source is a mixture of molybdenum trioxide powder and NaCl particles, the amount of molybdenum trioxide powder is 1-2 mg, and the amount of NaCl particles added is 0.5-1 mg.

[0014] Optionally, the SiO2 / Si substrate is 1 cm away from the molybdenum source.

[0015] Optionally, in step 4, before starting heating, purge with Ar at a flow rate of 600 sccm; then adjust the carrier gas flow rate to a constant 40 sccm.

[0016] Optionally, the inner diameter of the quartz test tube is 10 mm;

[0017] The outer diameter of the quartz tube is 25 mm.

[0018] Optionally, the cutting size of the SiO2 / Si substrate is 0.9 cm×3 cm.

[0019] Optionally, the growth time of the chemical vapor deposition is 5 to 10 minutes.

[0020] A three-layer twisted-angle MoS2 is prepared by any preparation method of the three-layer twisted-angle MoS2 described in the present invention.

[0021] Advantages of the present invention:

[0022] (1) This method can prepare three-layer twisted-angle MoS2 in one step. The prepared three-layer twisted-angle MoS2 material has a uniform surface, is pollution-free, and has high quality. The preparation process is simple and easy to operate.

[0023] (2) The reaction process can achieve torsional nucleation and growth of materials by finely adjusting reaction conditions such as reaction temperature, reaction time, heating rate, etc., and provides flexibility and designability for the growth rate, nucleation density, etc. of the material.

[0024] (3) The present invention can finely adjust the interlayer twist structure of three-layer MoS2 by adjusting the ratio of solidified and unsolidified sulfur powder, ensure the uniformity and high purity of the material, and reduce the generation of impurities during the reaction. When the ratio of solidified and unsolidified sulfur powder is 2:3, the sulfur source supply is more balanced. At this time, part of the sulfur in the sulfur powder has been solidified, providing a relatively stable sulfur source, while the unsolidified part of the sulfur provides sufficient reaction power for material growth. Since the uniformity and stability of the sulfur source supply are better at this time, each layer can obtain sufficient kinetic regulation during the growth process to ensure that each layer forms a structure with an interlayer twist angle. This method not only provides a simple and efficient way to prepare high-quality three-layer twist angle MoS2, but also provides a powerful tool for studying the strong coupling interlayer interaction in the moiré superlattice. By precisely controlling the interlayer twist structure, this method is expected to play a key role in regulating its unique correlated electronic properties and exciton-related multi-body effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:

[0026] Figure 1 It is a schematic diagram of the experimental preparation of the embodiments and comparative examples of the present invention;

[0027] Figure 2 This is an optical microscope photograph of Example 1 of the present invention;

[0028] Figure 3 is the Raman spectrum of Example 1 of the present invention;

[0029] Figure 4 The photoluminescence spectrum of Example 1 of the present invention;

[0030] Figure 5 This is an optical microscope photograph of Example 2 of the present invention;

[0031] Figure 6 is the Raman spectrum of Example 2 of the present invention;

[0032] Figure 7 The photoluminescence spectrum of Example 2 of the present invention;

[0033] Figure 8 This is an optical microscope photograph of Example 3 of the present invention;

[0034] Fig. 9 is the Raman spectrum of Example 3 of the present invention;

[0035] Fig.10 The photoluminescence spectrum of Example 3 of the present invention;

[0036] Fig.11 This is an optical microscope photo of Comparative Example 1 of the present invention;

[0037] Fig.12 is the Raman spectrum of Comparative Example 1 in the present invention;

[0038] Fig.13 Photoluminescence spectrum of Comparative Example 1 in the present invention. DETAILED DESCRIPTION

[0039] The present invention is described in detail below with reference to the accompanying drawings and specific implementation methods.

[0040] The three-layer twisted-angle MoS2 prepared by the present invention is grown directly on a SiO2 / Si substrate by chemical vapor deposition. By the sulfur source curing ratio control method, that is, precisely adjusting the curing ratio of the sulfur source and other factors, three-layer twisted-angle MoS2 materials with different stacking structures are obtained, with simple process and low cost.

[0041] The specific steps include:

[0042] Step 1: Heat the sulfur powder to 200°C until it is completely melted, and then cool and solidify naturally. Mix the solidified sulfur powder with fresh sulfur powder, put them in a quartz crucible, and place the quartz crucible in the heat radiation zone of a single temperature zone tube furnace.

[0043] Step 2: First, place two SiO2 / Si substrates in a quartz test tube with openings at both ends, then place evenly mixed molybdenum source and NaCl at the tube mouth, and place the quartz test tube in the center of a single-temperature zone tubular furnace.

[0044] Step 3: Seal the quartz tube and purge it with Ar at a flow rate of 600 sccm before starting heating. Then adjust the carrier gas flow rate to 40 sccm, and keep it constant during the entire chemical reaction.

[0045] Step 4: Set the temperature control program, control the heating rate at 30℃ / min, uniformly heat up to the maximum temperature of 800℃, and keep it at the maximum temperature, then cool naturally, and you can get three-layer twist angle MoS2 with different interlayer twist structures on the SiO2 / Si substrate.

[0046] In the embodiments of the present disclosure, the amount of sulfur source used is 1.0-3.0 g, of which the amount of sulfur powder solidified after heating is 0.6-2.4 g, the amount of fresh sulfur powder is 0.6-2.4 g, and the sulfur source extends into the furnace by 2.0-2.1 cm.

[0047] In the embodiments of the present disclosure, for twist-angle MoS2 with a twisted structure between all three layers, the ratio of solidified sulfur powder to uncured sulfur powder should be close to 2:3; for twist-angle MoS2 with only two layers having a twisted structure among the three layers, the ratio of solidified sulfur powder to uncured sulfur powder should be close to 4:1, 3:2, and 1:4.

[0048] In the embodiment of the present disclosure, the inner diameter of the quartz test tube is 25 mm, the molybdenum source is molybdenum trioxide powder and NaCl particles, the amount of molybdenum trioxide powder is 1-2 mg, and the amount of NaCl particles added is 0.5-1 mg.

[0049] In the embodiment of the present disclosure, a sulfur source is placed in the quartz tube according to the flow direction of the carrier gas, and a quartz test tube with both ends opened is arranged downstream of the sulfur source.

[0050] In the embodiment of the present disclosure, the cutting size of the SiO2 / Si substrate is 0.9 cm×3 cm.

[0051] In the embodiments of the present disclosure, two SiO2 / Si substrates are stacked with their silicon dioxide surfaces facing upward or downward, and a molybdenum source is placed 1 cm in front of the substrates. The molybdenum source is located near the gas inlet of the quartz tube.

[0052] In the examples of the present disclosure, the molybdenum source and the sulfur source are 12 cm apart.

[0053] In the embodiment of the present disclosure, the holding time of chemical vapor deposition is 5 to 10 minutes.

[0054] In order to make the purpose and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments, and the advantages of the present invention are reflected by analyzing the comparative examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0055] Embodiment 1:

[0056] The method for preparing three layers of twisted MoS2 with twisted structures between layers on a silicon dioxide / silicon substrate provided in this embodiment comprises the following steps:

[0057] Step 1: Cut the silica / silicon substrate into 0.9×3 cm sheets and blow them clean with an air gun. Place the silica surfaces back to back in a quartz test tube with openings at both ends and an inner diameter of 10 mm.

[0058] Step 2: Add 1 mg of molybdenum trioxide powder and place it 1 cm from the front of the substrate, and add 1 mg of NaCl to the molybdenum trioxide powder.

[0059] Step 3: Place the quartz test tube in a quartz tube with an outer diameter of 25 mm, add molybdenum trioxide powder and one end of NaCl close to the air inlet. Put 0.8g of sulfur powder solidified after heating and 1.2g of fresh sulfur powder into the quartz crucible as the S source, and extend it 2.0cm into the furnace. The S source and the molybdenum source are 12cm apart, and the chemical vapor deposition of the two-dimensional material twisted angle MoS2 is carried out in the heating center of the tubular atmosphere furnace, such as Figure 1 shown.

[0060] Step 4: Pass 600 sccm of argon gas for 10 minutes to completely remove the residual oxygen in the tube. Then continue to pass 40 sccm of argon gas, heat the tubular atmosphere furnace to 800℃ at a heating rate of 25℃ / min, and keep it warm for 5 minutes. Then cool it naturally to room temperature. The optical photo of the two-dimensional material MoS2 obtained at this time is as follows Figure 2 shown.

[0061] Depend on Figure 2 The optical photos show that the prepared material is a twisted MoS2 with twisted structures between the three layers. The twist angles of the first and second layers are 88°, and the twist angles of the second and third layers are 90°. Figure 3 As shown in the figure, positions 1, 2, and 3 all have Raman characteristic peaks of MoS2, indicating that the prepared material is MoS2. Figure 4As shown in the figure, two peaks are observed at 1.81eV and 1.93eV, representing A excitons and B excitons respectively. In the twisted-angle MoS2 with twisted structure between three layers, the A exciton peak is the strongest in a single layer. As the number of layers increases from double layers to triple layers, the position of the A exciton peak moves to lower energy and the intensity gradually increases, while the peak position of the B exciton peak remains unchanged. This shows that the photoluminescence properties of the twisted-angle MoS2 with twisted structure between three layers are affected by the combined effects of the number of layers and the twist angle effect, showing exciton behavior different from that of the single-layer material.

[0062] Embodiment 2:

[0063] The method for preparing twisted-angle MoS2 with only two layers having a twisted structure in three layers on a silicon dioxide / silicon substrate provided in this embodiment comprises the following steps:

[0064] Step 1: Cut the silica / silicon substrate into 0.9×3 cm sheets and blow them clean with an air gun. Place the silica surfaces back to back in a quartz test tube with openings at both ends and an inner diameter of 10 mm.

[0065] Step 2: Add 1 mg of molybdenum trioxide powder and place it 1 cm from the front of the substrate, and add 1 mg of NaCl to the molybdenum trioxide powder.

[0066] Step 3: Place the quartz test tube in a quartz tube with an outer diameter of 25 mm, add molybdenum trioxide powder and one end of NaCl close to the air inlet. Put 1.2g of sulfur powder solidified after heating and 0.8g of fresh sulfur powder into the quartz crucible as the S source, and extend it 2.1cm into the furnace. The S source and the molybdenum source are 12cm apart, and the chemical vapor deposition of the two-dimensional material twisted angle MoS2 is carried out in the heating center of the tubular atmosphere furnace, such as Figure 1 shown.

[0067] Step 4: Pass 600 sccm of argon gas for 10 minutes to completely remove the residual oxygen in the tube. Then continue to pass 40 sccm of argon gas, heat the tubular atmosphere furnace to 800℃ at a heating rate of 25℃ / min, and keep it warm for 5 minutes. Then cool it naturally to room temperature. The optical photo of the two-dimensional material MoS2 obtained at this time is as follows Figure 5 shown.

[0068] Depend on Figure 5 From the optical photographs, it can be seen that the prepared material is a twisted MoS2 with only two layers having a twisted structure. The moiré angle of the first and second layers is 80°, and the second and third layers have no twist angle. Figure 6 As shown in the figure, positions 1, 2, and 3 all have Raman characteristic peaks of MoS2, indicating that the prepared material is MoS2. Figure 7As shown in the figure, two peaks were observed at 1.81eV and 1.93eV, representing A excitons and B excitons respectively. In the twisted-angle MoS2 with only two layers having a twisted structure, the peak position of the B exciton in the third layer shifted toward the low energy direction compared to the second layer. This shows that the photoluminescence properties of this material are affected by the combined effects of the number of layers and the twist angle effect, showing different exciton behavior from the twisted-angle MoS2 with twisted structures between all three layers.

[0069] Embodiment three:

[0070] The method for preparing twisted-angle MoS2 with only two layers having a twisted structure in three layers on a silicon dioxide / silicon substrate provided in this embodiment comprises the following steps:

[0071] Step 1: Cut the silica / silicon substrate into 0.9×3 cm sheets and blow them clean with an air gun. Place the silica surfaces back to back in a quartz test tube with openings at both ends and an inner diameter of 10 mm.

[0072] Step 2: Add 1 mg of molybdenum trioxide powder and place it 1 cm from the front of the substrate, and add 1 mg of NaCl to the molybdenum trioxide powder.

[0073] Step 3: Place the quartz test tube in a quartz tube with an outer diameter of 25 mm, add molybdenum trioxide powder and one end of NaCl close to the air inlet. Put 0.6g of sulfur powder solidified after heating and 2.4g of fresh sulfur powder into the quartz crucible as the S source, and extend it 2.1cm into the furnace. The S source and the molybdenum source are 12cm apart, and the chemical vapor deposition of the two-dimensional material twisted angle MoS2 is carried out in the heating center of the tubular atmosphere furnace, such as Figure 1 shown.

[0074] Step 4: Pass 600 sccm of argon gas for 10 minutes to completely remove the residual oxygen in the tube. Then continue to pass 40 sccm of argon gas, heat the tubular atmosphere furnace to 800℃ at a heating rate of 25℃ / min, and keep it warm for 5 minutes. Then cool it naturally to room temperature. The optical photo of the two-dimensional material MoS2 obtained at this time is as follows Figure 8 shown.

[0075] Depend on Figure 8 From the optical photos, it can be seen that the prepared material is a twisted MoS2 with only two layers having a twisted structure. The moiré angle of the first and second layers is 99°, and the second and third layers have no twist angle. Fig. 9 As shown in the figure, positions 1, 2, and 3 all have Raman characteristic peaks of MoS2, indicating that the prepared material is MoS2. Fig.10As shown in the figure, two peaks were observed at 1.81eV and 1.93eV, representing A excitons and B excitons respectively. In the twisted-angle MoS2 with only two layers having a twisted structure, the peak position of the B exciton in the third layer shifted toward the low energy direction compared with the second layer. This shows that the photoluminescence properties of the material are affected by the combined effects of the number of layers and the twist angle effect, showing different exciton behavior from the twisted-angle MoS2 with twisted structures between all three layers.

[0076] Comparative Example 1:

[0077] This comparative example provides a method for preparing a two-dimensional material MoS2 without adjusting the ratio of solidified and fresh sulfur powder, comprising the following steps:

[0078] Step 1: Cut the silica / silicon substrate into 0.9×3 cm sheets and blow them clean with an air gun. Place the silica surfaces back to back in a quartz test tube with openings at both ends and an inner diameter of 10 mm.

[0079] Step 2: Add 1 mg of molybdenum trioxide powder and place it 1 cm from the front of the substrate, and add 1 mg of NaCl to the molybdenum trioxide powder.

[0080] Step 3: Place the quartz test tube in a quartz tube with an outer diameter of 25 mm, add molybdenum trioxide powder and one end of NaCl close to the air inlet. Put 2.5g of sulfur powder solidified after heating and 0.5g of fresh sulfur powder into the quartz crucible as the S source, and extend it 2.0cm into the furnace. The S source and the molybdenum source are 12cm apart, and the chemical vapor deposition of the two-dimensional material twisted angle MoS2 is carried out in the center of the tubular atmosphere furnace. Figure 1 shown.

[0081] Step 4: Pass 600 sccm of argon gas for 10 minutes to completely remove the residual oxygen in the tube. Then continue to pass 40 sccm of argon gas, heat the tubular atmosphere furnace to 800℃ at a heating rate of 25℃ / min, and keep it warm for 5 minutes. Then cool it naturally to room temperature. The optical photo of the two-dimensional material MoS2 obtained at this time is as follows Fig.11 shown.

[0082] Depend on Fig.11 Optical photos show that the prepared material is non-twisted MoS2, and the first and second layers and the second and third layers do not have a twist angle. Fig.12 As shown in the figure, positions 1, 2, and 3 all have Raman characteristic peaks of MoS2, indicating that the prepared material is MoS2. Fig.13As shown in the figure, two peaks were observed at 1.81eV and 1.93eV, representing A excitons and B excitons respectively. In the non-twisted MoS2, the peak positions of A and B excitons in the second and third layers were not shifted. This shows that the photoluminescence properties of this material are affected by the combined effects of the number of layers and the twist angle effect, showing different exciton behavior from the three-layer twisted MoS2.

[0083] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing three-layer twisted-angle MoS2, characterized in that: The preparation method comprises: Step 1: The preparation space is a closed quartz tube, carrier gas is introduced into both ends of the quartz tube, a quartz crucible is placed at the inflow end of the carrier gas, and sulfur powder is placed in the quartz crucible; Step 2: The Si surfaces of two SiO2 / Si substrates are laminated and stacked in a quartz test tube with openings at both ends, and a molybdenum source is placed in the tube, where the molybdenum source is located at the inflow end of the carrier gas; Step 3: The quartz test tube and the quartz crucible are both placed in the furnace of the heating furnace, the sulfur powder is heated to 200°C until it is completely melted, then naturally cooled and solidified, and the solidified sulfur powder is mixed with the sulfur powder; the amount of sulfur powder solidified after heating is 0.6-2.4g, the amount of sulfur powder is 0.6-2.4g, the total amount of sulfur powder is 1.0-3.0g, and the distance that the sulfur powder extends into the furnace is 2.0-2.1cm; Step 4: Set the temperature control program, control the heating rate at 25℃ / min, and after the temperature reaches 800℃ at a uniform rate, carry out material growth, and then cool naturally to obtain three-layer twisted MoS2 on the SiO2 / Si substrate.

2. The method for preparing three-layer twisted-angle MoS2 according to claim 1, characterized in that: For the twisted-angle MoS2 with twisted structures between all three layers, the ratio of sulfur powder to sulfur powder solidified after heating was 2:3; For twist-angle MoS2, where only two of the three layers have a twisted structure, the ratio of sulfur powder to sulfur powder solidified after heating is 4:1, 3:2, or 1:

4.

3. The method for preparing three-layer twisted-angle MoS2 according to claim 1 or 2, characterized in that: The sulfur source extends into the furnace by 2.0-2.1 cm; the molybdenum source and the sulfur source are 12 cm apart.

4. The method for preparing three-layer twisted-angle MoS2 according to claim 1 or 2, characterized in that: The molybdenum source is a mixture of molybdenum trioxide powder and NaCl particles, the amount of molybdenum trioxide powder is 1-2 mg, and the amount of NaCl particles added is 0.5-1 mg.

5. The method for preparing three-layer twisted-angle MoS2 according to claim 1 or 2, characterized in that: The SiO2 / Si substrate is 1 cm away from the molybdenum source.

6. The method for preparing three-layer twisted-angle MoS2 according to claim 1 or 2, characterized in that: In the fourth step, before starting heating, purge with Ar at a flow rate of 600 sccm; then adjust the carrier gas flow rate to a constant 40 sccm.

7. The method for preparing three-layer twisted-angle MoS2 according to claim 1 or 2, characterized in that: The inner diameter of the quartz test tube is 10 mm; The outer diameter of the quartz tube is 25 mm.

8. The method for preparing three-layer twisted-angle MoS2 according to claim 1 or 2, characterized in that: The cutting size of the SiO2 / Si substrate is 0.9 cm×3 cm.

9. The method for preparing three-layer twisted-angle MoS2 according to claim 1 or 2, characterized in that: The growth time of the chemical vapor deposition is 5 to 10 minutes.

10. A three-layer twisted-angle MoS2, characterized in that: The three-layer twisted-angle MoS2 is prepared by the preparation method of any one of claims 1-9.